Association of ELMO1 Genetic Polymorphism (rs741301) with the Progression of Diabetic Kidney Disease in Balinese Patients with Type 2 Diabetes Mellitus - Anak Agung Istri Kaila Kirtaniya; Asri Lestarini; Pande Ayu Naya Kasih Permatananda; Anak Agung Sri Agung Aryastuti (Molecular and Cellular Biomedical Sciences, 2023)
Background: Diabetic kidney disease (DKD) is one of diabetes mellitus microvascular complications. Engulfment and cell motility 1 (ELMO1) protein interacts with dedicator of cytokinesis 180 (DOCK180) and cyclooxygenase (COX)-2, which affects gene expression in extracellular matrix (ECM) and causes glomerular damage in several mechanisms, such as ECM accumulation and renal tubules thickening. Single nucleotide polymorphism (SNP) rs741301 is one of the ELMO1 genetic polymorphisms involved in DKD. The aim of this study was to evaluate the association between ELMO1 rs741301 polymorphism and DKD in type 2 diabetes mellitus (T2DM) among Balinese.Materials and methods: This study was an observational analytical study with case-control method. Subjects were divided into control and case groups comprising 40 subjects each. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) of DNA from T2DM patients were performed to detect the polymorphism in ELMO1 rs741301. Genotype and allele distribution obtained from this study was analyzed by chi-square (χ2) test and Hardy-Weinberg equilibrium law (p<0.05; CI: 95%).Results: There was no significant difference between genotype or allele distribution of ELMO1 rs741301 with DKD incidence. Genotype AA against GG had odds ratio (OR) of 0.793 (p=0.814), AG against GG had OR of 0.602 (p=0.674), and A allele against G allele had OR of 0.761 (p=0.509).Conclusion: There is no significant relationship between ELMO1 rs741301 polymorphism and DKD in T2DM patients among Balinese.Keywords: ELMO1 gene, diabetic kidney disease, polymorphism